Organosulfur Compounds: A Review of Their Anti-inflammatory Effects in Human Health - Ruhee, Ruheea Taskin; Roberts, Llion Arwyn; Ma, Sihui; Suzuki, Katsuhiko (Frontiers in Nutrition, 2020)
Phytonutrients are widely recognized for providing protective human health benefits. Among the phytonutrients, epidemiological and experimental studies show that dietary organosulfur compounds (OSC) play a significant role in preventing various human pathological progressions, including chronic inflammation, by decreasing inflammatory mediators such as nitric oxide (NO), prostaglandin (PG)E2, interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, and IL-17, which are all typical hallmarks of inflammation. Evidence supports OSC in reducing the expression of these markers, thereby attenuating chronic inflammatory processes. Nuclear factor-kappa B (NF-κB) is a key regulating factor during inflammation, and novel evidence shows that OSC downregulates this transcriptional factor, thus contributing to the anti-inflammatory response. In vitro and in vivo studies show that inflammation is mechanistically linked with acute and chronic pathological conditions including cancer, diabetes, obesity, neural dysfunction, etc. Furthermore, a considerable number of experiments have demonstrated that the anti-inflammatory properties of OSC occur in a dose-dependent manner. These experiments also highlight indirect mechanisms as well as potent co-functions for protective roles as antioxidants, and in providing chemoprotection and neuroprotection. In this brief review, we provided an overview of the anti-inflammatory effects of OSC and elucidated probable mechanisms that are associated with inflammation and chronic disorders.